Apakah Desain Eksperimen Satu Kelompok Layak Digunakan? - Ahmad Saifuddin (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Research is a form of effort to achieve truth. Research is divided into several methods, namely qualitative, quantitative, and mixed method. Each of these research methods includes several research techniques, one of which is experimental research. Experimental research including quantitative research methods. Broadly speaking, experimental research is divided into pre-experiment, quasi experiment, and true experiment. Many studies still use a one-group design. This study aims to assess the feasibility of one group design using a literature study. The result is that the experimental design of one group is considered less suitable for use in research due to several factors, namely the minimal number of groups, no control group, not random, and low validity.